BUSINESS ACTIVITIES OF BANK WAKAF MIKRO: CRIMINAL LAW POLICY IN THE IMPLEMENTATION OF MICROFINANCE INSTITUTIONS IN INDONESIA - Aminullah, Bayu Ardian; Jaya, Nyoman Serikat Putra (Tadulako University, 2021)
The purpose of this research is to determine the legal provisions of the implementation of Bank Wakaf Mikro as a Microfinance Institution, as well as to find out the criminal law policy in Bank Wakaf Mikro business activities. This research uses a normative legal research method with a statutory approach. This research shows that the Bank Wakaf Mikro is to overcome the problem of poverty and social inequality that occurs in society by empowering productive businesses that can be directly managed by the community. Bank Wakaf Mikro can be defined as a special financial institution established to provide business development and community empowerment services, through financing in micro-scale businesses to members and the community, managing savings, as well as providing business development consulting services by applying sharia principles that are not solely seeking advantage. Bank Wakaf Mikro is regulated in Law Number 1 of 2013 concerning Microfinance Institutions and the criminal provisions in the business activities of Bank Wakaf Mikro are regulated in the provisions of Chapter XII Articles 34 to 38.